Effect of Job Insecurity, Working Conditions and Compensation on Turnover Intention of New Tweety Magetan Bakeries Employees - Eka Agustina; Isharijadi Isharijadi; Farida Styaningrum (Universitas Merdeka Madiun, 2021)
This study aims to determine the effect of Job Insecurity, Working Conditions and Compensation for Turnover Intention on New Tweety Magetan Bakeries Employees. This study used descriptive statistical analysis and data collection used primary data through distributing questionnaires to respondents and secondary data, namely a list of employee names. The analytical method used is multiple linear regression with the help of SPSS version 25. This study shows that job insecurity has a positive and significant effect on turnover intention, work conditions have a negative and significant effect on turnover intention, and compensation has a negative and significant effect on turnover intention in New Tweety Magetan bakery employee.